Miscellaneous estrays relating to Rex Nan Kivell - Nan Kivell, Rex, 1898-1977.; Victoria. Agent General; New Zealand Founders Society (1909)
MS Acc11.185 is a small collection of four items relating to Rex Nan Kivell. It comprises an invitation from the Agent General of Victoria to the opening of the new offices of the Government of Victoria at The Strand on 30 March, 1909; manuscript address on behalf of the General Assembly of the Presbyterian Church in Western Australia welcoming Sir Francis Newdegate as governor of Western Australia in 1920; flyer of the New Zealand Founders Society Inc. inscribed by the Society’s founder D. Hope Johnston, London, 1950; and, a colour postcard depicting the "Cutty Sark" addressed to Rex Nan Kivell in Morocco from Joyce Gibson, dated 16 July, 1975 (1 packet).
Manuscript reference no.: MS Acc11.185.
Rex Nan Kivell Collection NK4183.
Rex Nan Kivell was a director of the Redfern Gallery, London. Born in New Zealand, he had a keen interest in Australian, New Zealand and Pacific paintings, prints, books and manuscripts. In June 1966 he was granted a CMG for services in providing the National Library of Australia with valuable early Australian and Pacific paintings and manuscripts.
Keywords: Nan Kivell, Rex, -- 1898-1977 -- Archives; Newdegate, Francis, -- Sir, -- 1862-1936.; Cutty Sark (Ship) -- Photographs; Governors -- Western Australia; Diplomatic and consular service, Australian -- Great Britain; Embassy buildings -- England -- London; Western Australia -- Politics and government -- 1901-1945.; New Zealand -- History -- 1840-1853.; Collectors; Art gallery directors